Evaluation of Carbapenem Use Before and After Implementation of an Antimicrobial Stewardship-Led Carbapenem-Sparing Strategy in a Lebanese Tertiary Hospital: A Retrospective Study - El Masri, Mira; Haddad, Nisrine; Saad, Therese; Rizk, Nesrine A.; Zakhour, Ramia; Kanj, Souha S.; Zeenny, Rony M. (Frontiers in Cellular and Infection Microbiology, 2022)
Purpose. The use of carbapenem before and after implementation of an antimicrobial stewardship-led carbapenem-sparing strategy at a tertiary care center in Lebanon was evaluated. Methods. A retrospective, observational chart review was performed on all hospitalized pediatric and adult patients who received carbapenem therapy during January 2019 and January 2020. Patients who started their regimen before January or received carbapenems for less than 24 hours were excluded. Primary outcomes included the appropriateness of physician prescribing patterns and pharmacists’ interventions, as well as appropriateness and response rates of the latter. Secondary outcomes included the carbapenem defined daily dose (DDD) and days of therapy (DOT). Descriptive statistics were used in the analysis and a p-value < 0.05 was considered to be statistically significant. Results. A total of 157 and 150 patients charts were reviewed in January 2019 and January 2020, respectively. There was no difference in baseline characteristics except for inpatient services and rates of isolated multidrug-resistant organisms. When comparing the two timelines, the appropriateness of physicians’ prescribing patterns increased in terms of empirical therapy, targeted therapy, and duration of therapy but the results were not statistically significant. Pharmacists’ interventions significantly increased with regards to the duration of therapy (p= <0.001), dose adjustment (p<0.001), de-escalation to a narrower spectrum antibiotic (p=0.007), and use of extended infusion (p=0.042). The DDD and DOT were higher for ertapenem and lower for anti-pseudomonal carbapenems in January 2020. Conclusion. The carbapenem-sparing strategy adopted by the antimicrobial stewardship program contributed to an increase in the number of interventions made by pharmacists on carbapenem therapy, including their appropriateness, and response rate. Despite an improvement in the physician-prescribing patterns, more awareness and education may be needed to achieve a better impact.